Can the outcome of acute pancreatitis be improved in intensive care unit?: a collaborative study - Atilla SORAN; Cavit ÇÖL; Belma KOÇER; Lakshmipathi CHELLURI; Kenneth KW. LEE; Deniz AYDIN; Samuel A. TISHERMAN (Turkish Journal of Gastroenterology, 2019)
-